Structural characterization and functional properties of antihypertensive Cymodocea nodosa sulfated polysaccharide. (20th October 2016) - Kolsi, Rihab Ben Abdallah; Fakhfakh, Jawhar; Krichen, Fatma; Jribi, Imed; Chiarore, Antonia; Patti, Francesco Paolo; Blecker, Christophe; Allouche, Noureddine; Belghith, Hafedh; Belghith, Karima
Highlights: This is the first report on the sulfated polysaccharide from Cymodocea nodosa seagrass. Structure of the polysaccharide was established by FT-IR, GC–MS, NMR, LC–ESI–MS/MS. The monosaccharide composition showed the abundance of galactose sugar. A backbone of branched 6-O-sulfated (1 → 4)-galactosidic linkages was indicated. Antihypertensive activity in vitro was determined. Abstract: A sulfated polysaccharide was successfully isolated from Cymodocea nodosa (CNSP). This is the first report that indicates the chemical composition, structural characterization, functional and antihypertensive properties of this polysaccharide. The CNSP consisted mainly of sulfate (23.17%), total sugars (54.90%), galactose (44.89%), mannose (17.30%), arabinose (12.05%), xylose (9.18%), maltose (1.07%) and uronic acid (11.03%) with low water activity (0.49). CNSP had an XRD pattern that was typical for a semi-crystalline polymer with homogeneous structure. It also displayed an important anti-hypertensive activity (IC50  = 0.43 mg ml) with a dose-dependent manner using a synthetic substrate, N-hippuryl-His-Leu hydrate salt (HHL). Overall, the results indicate that CNSP have attractive chemical, functional and biological properties, with a preliminary structural may have a backbone of branched 6-O-sulfated (1 → 4) galactosidic linkages, which can be considered in the future as alternative additive in various foods, cosmetic and pharmaceutical preparations.